Mixed Bacillus subtilis and Lactiplantibacillus plantarum-fermented feed improves gut microbiota and immunity of Bamei piglet - Chen, Jun; Mou, Liyu; Wang, Lei; Wu, Guofang; Dai, Ximei; Chen, Qiufang; Zhang, Jianbo; Luo, Xuan; Xu, Fafang; Zhang, Miao; Duan, Yaoke; Pang, Huili; et al. (Frontiers in Microbiology, 2024)
Antibiotics are widely used in the breeding production of Bamei pigs, affecting the quality and safety of pork and causing enormous harm to human health, the environment, and public health. The use of probiotic fermented feed to replace antibiotic feed is one of the solutions, which has the potential to improve the intestinal microbiota, promote animal growth, and enhance immunity. The purpose of this study was to evaluate the effect of fermented feed with Lactiplantibacillus (L.) plantarum QP28-1a or Bacillus (B.) subtilis QB8a on feed, growth performance, gut microbiota, and immunity of weaned piglets. A total of 60 freshly weaned pigspiglets from the Tibetan Plateau were randomly divided into five groups and fed basal feed, L. plantarum fermented feed, B. subtilis fermented feed, mixed fermented feed, and antibiotic fermented feed for 60 days, respectively. The results showed fermented feed supplemented with L. plantarum QP28-1a or B. subtilis QB8a significantly lowered the pH of the feed (P<0.05), produced lactic acid and acetic acid, inhibited the growth of harmful bacteria in the feed, and reduced the feed conversion rate was reduced in the group fed mixed fermented feed (P<0.05). The fermented feed increased the α-diversity and prominently altered the β-diversity of the intestinal microbiota, increasing the relative abundance of beneficial bacteria such as LactoBacillus Lactobacillus and Turicibacter and decreasing the relative abundance of conditional pathogens such as Streptococcus and Clostridium, improving the intestinal microbiota of the Bamei pigspiglets. Notably, the mixed fermented feed improved the immunity of Bamei pigspiglets by modulating the production of pro-inflammatory cytokines, anti-inflammatory cytokines, and inflammatory-related signaling pathways. Spearman's correlation analysis revealed that the increased expression of immunerelated cytokines may be associated with a significant enrichment of LactoBacillusLactobacillus,